Genetic Determinants of Pelvic Organ Prolapse among African American and Hispanic Women in the Women's Health Initiative. - Ayush Giri; Jennifer M Wu; Jennifer M Wu; Renee M Ward; Katherine E Hartmann; Amy J Park; Kari E North; Mariaelisa Graff; Robert B Wallace; Gihan Bareh; Lihong Qi; Mary J O'Sullivan; et al. (PLoS ONE)
Current evidence suggests a multifactorial etiology to pelvic organ prolapse (POP), including genetic predisposition. We conducted a genome-wide association study of POP in African American (AA) and Hispanic (HP) women from the Women's Health Initiative Hormone Therapy study. Cases were defined as any POP (grades 1-3) or moderate/severe POP (grades 2-3), while controls had grade 0 POP. We performed race-specific multiple logistic regression analyses between SNPs imputed to 1000 genomes in relation to POP (grade 0 vs 1-3; grade 0 vs 2-3) adjusting for age at diagnosis, body mass index, parity, and genetic ancestry. There were 1274 controls and 1427 cases of any POP and 317 cases of moderate/severe POP. Although none of the analyses reached genome-wide significance (p<5x10-8), we noted variants in several loci that met p<10-6. In race-specific analysis of grade 0 vs 2-3, intronic SNPs in the CPE gene (rs28573326, OR:2.14; 95% CI 1.62-2.83; p = 1.0x10-7) were associated with POP in AAs, and SNPs in the gene AL132709.5 (rs1950626, OR:2.96; 95% CI 1.96-4.48, p = 2.6x10-7) were associated with POP in HPs. Inverse variance fixed-effect meta-analysis of the race-specific results showed suggestive signals for SNPs in the DPP6 gene (rs11243354, OR:1.36; p = 4.2x10-7) in the grade 0 vs 1-3 analyses and for SNPs around PGBD5 (rs740494, OR:2.17; p = 8.6x10-7) and SHC3 (rs2209875, OR:0.60; p = 9.3x10-7) in the grade 0 vs 2-3 analyses. While we did not identify genome-wide significant findings, we document several SNPs reaching suggestive statistical significance. Further interrogation of POP in larger minority samples is warranted.